2019
DOI: 10.1128/iai.00164-19
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand White Rabbits Effectively Clear Borrelia burgdorferi B31 despite the Bacterium’s FunctionalvlsEAntigenic Variation System

Abstract: Borrelia burgdorferi is a tick-borne bacterium responsible for approximately 300,000 annual cases of Lyme disease (LD) in the United States, with increasing incidences in other parts of the world. The debilitating nature of LD is mainly attributed to the ability of B. burgdorferi to persist in patients for many years despite strong anti-Borrelia antibody responses. Antimicrobial treatment of persistent infection is challenging. Similar to infection of humans, B. burgdorferi establishes long-term infection in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 119 publications
(211 reference statements)
0
15
0
Order By: Relevance
“…several surface proteins of B. burgdorferi have been identified. Interestingly, the newly identified epitopes are distinct from those recently delineated via the mouse repeated immunization assay (58). Importantly, when available, the published data cited below have empirically demonstrated that newly identified PA epitopes are surface exposed and that their respective proteins are considered to be strong LD vaccine candidates.…”
Section: Figmentioning
confidence: 85%
See 4 more Smart Citations
“…several surface proteins of B. burgdorferi have been identified. Interestingly, the newly identified epitopes are distinct from those recently delineated via the mouse repeated immunization assay (58). Importantly, when available, the published data cited below have empirically demonstrated that newly identified PA epitopes are surface exposed and that their respective proteins are considered to be strong LD vaccine candidates.…”
Section: Figmentioning
confidence: 85%
“…In contrast to the 50% protection rate achieved for mice via repeated immunization with the ΔVlsE mutant (59), the rabbit antibodies consistently prevented 100% of mice from host-adapted, VlsE-expressing spirochetes. Moreover, the rabbit antibodies significantly reduced the pathology of LD arthritis in persistently infected mice (58). Thus, in the present work, via subtractive RV (58), we have compared the antibody repertoires of nonprotective (day 14) and protective (day 28) rabbit sera with the goal of identifying the specificities of protective antibodies and, therefore, their respective surface targets.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations